THE EFFECT OF HEALTHY LIVING EDUCATION ON REDUCING BLOOD PRESSURE IN ELDERLY PEOPLE WITH HYPERTENSION - Apriyana, Eka; Indawati, Eli (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background: Background: Hypertension is where a person experiences an increase in blood pressure from the normal limit, where diastolic blood pressure is more than 140 mmHg and diastolic blood pressure is more than 90 mmHg. Self-management of hypertensive patients is a person's ability to maintain healthy living behavior to reduce blood pressure in elderly patients with hypertension in Kampung Warga I Cilangkap Cipayung, East Jakarta. This type of research is pre-experimental design research with a one group pre test-post test design approach. The sampling technique is non-probability sampling with a purposive sampling method with a sample size of 30 respondents. The instrument used is an intervention. Research Objective: To determine the effect of healthy living education on reducing blood pressure in elderly people with hypertension. This type of research is pre-experimental design research with a one group pre test-post test design approach. The parametric statistical test is the Wilcoxon test Research Results: Based on the results of the Wilcoxon statistical test in table 5.6, data on pre-post intervention systolic blood pressure was obtained, it was found that of the 30 respondents there were 22 people who experienced a decrease in systolic pressure (Negative rank), 3 respondents experienced an increase in blood pressure (Positive rank) and 5 people had constant blood pressure (Ties). Meanwhile, for the pre-test diastole, of the 30 respondents, 17 people experienced a decrease in diastolic pressure (Negative rank), 4 experienced an increase in diastolic pressure (Positive rank) and 9 people had constant blood pressure (Ties) and for systolic blood pressure the P value (ρ value) was 0.004 which means the overall value or total of everything. This means that there is an influence of healthy living education on reducing blood pressure in hypertensive patients in Warga Village I Cilangkap Cipayung. Conclusions and Suggestions: There is an influence of healthy living education on reducing blood pressure in elderly people with hypertension. It is hoped that the results of this study can increase